Does religiosity matter to value relevance?: evidence from U.S. banking firms - Chourou, Lamia (Journal of business ethics, 2020)
This study examines whether religiosity is associated with the valuation multiples investors assign to fair-valued assets that are susceptible to managerial bias. Using a sample of U.S. banking firms, I find that the value relevance of such assets is higher for firms located in more religious counties than it is for firms located in less religious counties. Moreover, I find that this result is more consistent with the ethicality trait than the risk aversion trait of more religious individuals. Additional tests show that the positive association between religiosity and value relevance of fair-valued assets is limited to firms with high fair value exposure, and it is stronger for firms with lower audit quality, lower institutional ownership, and lower analyst following. The results of this study suggest that investors perceive the role played by religiosity, in particular ethicality, in curbing managerial accounting biases and price accounting estimates accordingly.